2018 CNHP partners meeting - Colorado Natural Heritage Program, author (Colorado State University. Libraries, 2018)
At our 2018 Partners Meeting we discussed improving access to conservation data, addressing climate change, and expanding services to the private lands conservation community. We have a new strategic plan that addresses these priorities, and for this meeting all three of the main panels examined these topics and engaged in conversations on how we will move forward to address these as a community.
The 2018 CNHP Partners Meeting was held on March 9, 2018 in the Grand Ballroom D, Lory Student Center, Colorado State University Campus, Fort Collins, Colorado.
Keywords: Colorado; conservation; environment; stewardship